Studies into the mechanisms of the cross-country ski vibrations and possible models of the phenomenon - Koptyug, A.; Bäckström, M.; Tinnsten, M. (Procedia Engineering, 2013)
Field and laboratory measurements show a presence of intense cross-country ski vibrations during free gliding. There are indications that such vibrations may and indeed do affect the average friction forces and thus should affect the ski gliding. Our studies into the nature of these vibrations and the factors influencing their frequencies and magnitudes are driven by the desire to control them for improving ski gliding performance. The complexity of the corresponding resonance system, represented by constant interaction of the skier, the skis and the snow, and the mechanisms of the vibration excitation, most probably dominated by the stochastic forces caused by a stick-slip character of the friction, demand new approaches to the modelling and experiments. Present paper describes some results of the experimental laboratory studies of such vibrations, and possible approaches to their modelling following the routes suggested in modelling of the similar phenomena.